Psychotria bangueyensis - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Psychotria bangueyensis is restricted to three islands of Sabah, namely Banggi Island, Balambangan Island. and Tiga Island. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 12 km2 and 2,493 km2, respectively. It is protected in situ in Tun Mustapha Park and Pulau Tiga Park. However, some parts of the islands have been proposed for limestone mining as in Balambangan Island which will cause loss in native flora and fauna. Forest fire and human encroachment are also a concern to the vegetation of these islands. If these occur it could drive the species towards Critically Endangered or Extinct in the near future. The species is globally assessed as Vulnerable. Psychotria bangueyensis is endemic to Sabah, Malaysia. It is restricted to Pulau Tiga, Pulau Bangi and Pulau Balambangan at the west and north of Sabah. Country Occurrence.